Analysis of The Concept of Global Positioning System and Location Based Services to Make A Marking Mapping Mobile - Cholifah S; Sukoco A (International Conference on Engineering and Technology Development (ICETD), 2017)
Information technology is increasingly developed and developing all the time, has a very important role in all aspects of all wildlife. One aspect of the emerging technology is mobile technology on smartphone devices (smartphones).One of the technologies being busy discussed smartphone is Android. Android is an operating system for smartphones. It is built based on the Linux kernel that has beenmodified so that it is suitable for use in mobile phones or other handheld devices. Today more and more people are using the Android operating system, almost all walks of society to use it.To determinethe nearest lane to use API in Google Map.The author took the initiative to create a concept of mapping the position and distance calculator for smartphones with Android plat-form. This conceptutilizes Google Maps as map and GPS service embedded on smartphones to determine the location and calculation distance. (Mapping Location Based Service (LBS) Android-Based Bengkulu, ISSN,2014, Lia Astari, Khairil). In the process of marking a mobile mapping there are methods that can be used algorithm devicebased(LBS based tool). The algorithm is based on the GPS device on the phone.Mobile phones rely on the ability of the GPS device.